Labeling and Efficiency of Induction Motors, Iec on Chilean Case - Ojeda-Reyes, O; Becker-Cares, C; Verdejo-Fredes, H (IEEE Computer Society, 2015)
This article presents the historical development of a labeling program, particularly in Chile, the criteria chosen for the experiments, the participants of the process and the difficulties found during its execution. It also discussed the methodology used, which considered the IEC 60034-2-1 norm for direct and indirect measurements of the performance of three-phase induction motors. Finally, the results obtained by measuring the performance of one motor. Furthermore, not only the results are presented in a labeling context but also the criteria that they should meet for this class of program are suggested. © 2015 IEEE.